A high cycle life lithium ion battery negative electrode sheet and a preparation method thereof

CN122968240APending Publication Date: 2026-10-23GUOKE ENERGY TECH INNOVATION CENT (HEFEI) CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611029133.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-10
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0004]本发明提供一种高循环寿命锂离子电池负极极片及其制备方法,可以解决现有技术中负极极片难以同时兼顾低电阻率、优异柔韧性和高循环寿命的问题

Benefits of technology

1、本发明通过将负极浆料的固含量控制在49%-54%的适宜范围,保证了涂布过程的流动性与干燥效率的平衡;其中,石墨作为主体活性物质提供高容量,其含量94.6-97.5%确保了能量密度;炭黑0.5-1.2%作为辅助导电剂填充颗粒间隙,初步构建基础导电网络;改性碳纳米管0.05-0.1%凭借其一维长径比和表面功能化设计,与炭黑协同形成线-点立体导电骨架,显著降低极片电阻率;聚丙烯酸0.8-1.4%以其羧基与铜箔形成强氢键,同时与改性碳纳米管表面的活性基团相互作用,赋予极片高剥离强度和柔韧性;羧甲基纤维素钠0.1-1.5%作为增稠分散剂,调节浆料粘度、防止颗粒沉降;丁苯橡胶0.8-1.2%进一步增强粘结网络,提升极片加工性和循环稳定性。各组分在该特定配比下协同作用,共同实现了低电阻率、高剥离力、优异柔韧性和长循环寿命的综合性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122968240A_ABST
    Figure CN122968240A_ABST
Patent Text Reader

Abstract

The application discloses a kind of high cycle life lithium ion battery negative pole piece and preparation method thereof, belong to lithium ion battery technical field.The negative pole piece includes copper foil and negative pole slurry, the slurry contains 49-54% negative pole solid substance, the balance is water;Solid component is as follows according to weight percentage: graphite 94.6-97.5%, carbon black 0.5-1.2%, modified carbon nanotube 0.05-0.1%, polyacrylic acid 0.8-1.4%, sodium carboxymethyl cellulose 0.1-1.5%, butyl rubber 0.8-1.2%, and the sum of each component is 100%.The application utilizes the synergistic effect of modified carbon nanotube and PAA, reduces resistivity through three-dimensional conductive network, combines strong hydrogen bond bonding and bridging toughening, significantly improves the peel strength and anti-cracking performance of pole piece, effectively inhibits the shedding of active material during cycle process, and greatly improves the cycle life of battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium-ion battery technology, and in particular to a high cycle life lithium-ion battery negative electrode and its preparation method. Background Technology

[0002] Lithium-ion batteries are widely used in portable electronic devices, electric vehicles, and energy storage systems due to their high energy density, long cycle life, and environmental friendliness. The negative electrode is a core component of a lithium-ion battery, and its performance directly affects the battery's energy density, rate performance, and cycle life. Currently, lithium-ion battery negative electrodes typically use graphite as the active material, combined with an SBR (styrene-butadiene rubber) + CMC (sodium carboxymethyl cellulose) binder system and conductive carbon black as a conductive agent.

[0003] However, existing technologies still have the following drawbacks: conductive carbon black is a zero-dimensional particle, forming a point-to-point contact conductive mode in the electrode, resulting in high contact resistance and difficulty in constructing a continuous three-dimensional conductive network. This leads to high electrode resistivity, affecting rate performance and cycle polarization. With increasing areal density, the electrode lacks flexibility, making it prone to cracking and powdering during coating and rolling. In the traditional CMC+SBR system, CMC is hard and brittle, while SBR is prone to swelling, causing the active material to detach from the current collector. Although polyacrylic acid (PAA) binders can form strong hydrogen bonds through carboxyl groups, improving bond strength and cycle life, their coating films are brittle and cannot meet the crack resistance requirements of high areal density coatings when used alone. Therefore, developing a negative electrode with low resistivity, excellent flexibility, and high cycle life, and its preparation method, is of great significance. Summary of the Invention

[0004] This invention provides a high cycle life lithium-ion battery negative electrode sheet and its preparation method, which can solve the problem that the negative electrode sheet in the prior art is difficult to simultaneously achieve low resistivity, excellent flexibility and high cycle life.

[0005] The objective of this invention can be achieved through the following technical solutions: In a first aspect, the present invention provides a high cycle life lithium-ion battery negative electrode sheet, comprising a negative electrode slurry and copper foil; the negative electrode slurry comprises the following components by weight percentage: 49%-54% negative electrode solid material, the balance being deionized water; the negative electrode solid material comprises the following components by weight percentage: graphite 94.6-97.5%, carbon black 0.5-1.2%, modified carbon nanotubes 0.05-0.1%, polyacrylic acid 0.8-1.4%, sodium carboxymethyl cellulose 0.1-1.5%, styrene-butadiene rubber 0.8-1.2%; the sum of the weight percentages of all components of the negative electrode solid material is 100%.

[0006] Furthermore, the polyacrylic acid has a weight-average molecular weight of 300,000-800,000 and a glass transition temperature of 90-110°C.

[0007] Furthermore, the method for preparing the modified carbon nanotubes is as follows: S1. Dissolve citric acid and 3-amino-2-sulfopropionic acid in deionized water, sonicate until dissolved, heat to react, let stand, cool to room temperature, filter and collect the filtrate to obtain carbon dots; S2. Mix N-CNTs and carbon dots, ultrasonically stir, centrifuge, and dry to obtain N-CNTs-carbon dots; S3. Add N-CNTs-carbon dots to deionized water, stir, then add mercapto-polyethylene glycol silane, stir to react, filter, and dry to obtain modified carbon nanotubes.

[0008] Further, in step S1, the ratio of citric acid, 3-amino-2-sulfopropionic acid, and deionized water is 5g:4-5g:50mL.

[0009] Furthermore, in step S1, the heating reaction is carried out at a temperature of 170-190°C for 5-8 hours.

[0010] Further, in step S2, the method for preparing the N-CNTs is as follows: S21. Add multi-walled carbon nanotubes to nitric acid, stir to react, wash, and dry to obtain carbon oxide nanotubes. S22. Add carbon nanotubes and melamine to an aqueous ethanol solution, stir until the solvent is completely evaporated, anneal under nitrogen, wash, and dry to obtain N-CNTs.

[0011] Further, in step S21, the ratio of the amount of multi-walled carbon nanotubes to nitric acid is 1g:80-100mL.

[0012] Furthermore, in step S21, the temperature of the stirring reaction is 70-80℃, and the time is 5-7h.

[0013] Further, in step S22, the ratio of the amount of carbon nanotubes, melamine, and ethanol aqueous solution is 1g:0.6-0.8g:100mL; the volume ratio of anhydrous ethanol to deionized water in the ethanol aqueous solution is 1:1.

[0014] Furthermore, in step S22, the stirring temperature is 80°C; the annealing temperature is 650-700°C, and the time is 1-2 hours.

[0015] Further, in step S2, the ratio of N-CNTs to carbon dots is 1g:80-100mL.

[0016] Further, in step S3, the ratio of N-CNTs-carbon dots, deionized water, and mercaptopolyethylene glycol silane is 1g:10mL:0.05-0.1g.

[0017] Furthermore, in step S3, the stirring reaction is carried out at room temperature for 6-8 hours.

[0018] Secondly, the present invention provides a method for preparing a high cycle life lithium-ion battery negative electrode sheet, comprising the following steps: (1) Add polyacrylic acid to deionized water and stir to dissolve for 2 hours to prepare a glue solution with a solid content of 1%-3%; (2) Take 70% of the total amount of graphite and add it to the mixing tank along with all the conductive carbon black and all the sodium carboxymethyl cellulose. Then add deionized water and modified carbon nanotubes, knead and stir, then add the remaining 30% of graphite and continue stirring until uniform. Finally, add styrene-butadiene rubber and stir evenly to obtain the composite slurry. (3) Add 20% of the total amount of adhesive to the composite slurry, stir and disperse, then add the remaining 80% of adhesive, adjust the viscosity, and degas under vacuum to obtain the negative electrode slurry; (4) The negative electrode slurry is coated onto copper foil, dried, and then rolled to obtain the negative electrode sheet.

[0019] Further, in step (3), the viscosity is 4000-8000 mPa·s.

[0020] The beneficial effects of this invention are: 1. This invention ensures a balance between fluidity and drying efficiency during the coating process by controlling the solid content of the negative electrode slurry within a suitable range of 49%-54%. Graphite, as the main active material, provides high capacity, with a content of 94.6-97.5% ensuring energy density. Carbon black (0.5-1.2%) acts as an auxiliary conductive agent, filling the interparticle gaps and initially constructing a basic conductive network. Modified carbon nanotubes (0.05-0.1%), with their one-dimensional aspect ratio and surface functionalization design, synergistically form a line-point three-dimensional conductive framework with carbon black, significantly reducing electrode resistivity. Polyacrylic acid (0.8-1.4%) forms strong hydrogen bonds with copper foil through its carboxyl groups, while also interacting with the active groups on the surface of modified carbon nanotubes, giving the electrode high peel strength and flexibility. Sodium carboxymethyl cellulose (0.1-1.5%) acts as a thickener and dispersant, adjusting slurry viscosity and preventing particle sedimentation. Styrene-butadiene rubber (0.8-1.2%) further enhances the bonding network, improving electrode processability and cycle stability. The components work synergistically in this specific ratio to achieve a combination of low resistivity, high peel strength, excellent flexibility, and long cycle life.

[0021] 2. The core of this technology lies in the synergistic effect of PAA and modified carbon nanotubes: First, by utilizing the high aspect ratio of modified carbon nanotubes, a three-dimensional conductive framework with line-to-point contact is formed between graphite particles, replacing the point-to-point contact mode of traditional conductive carbon black, significantly reducing the electrode resistivity and constructing a highly efficient three-dimensional conductive network; Second, as an aqueous binder, the carboxyl groups (-COOH) on the PAA molecular chain form strong hydrogen bonds with the copper foil surface, greatly improving the electrode peel strength; At the same time, the fibrous structure of modified carbon nanotubes plays a bridging and toughening role in the electrode, effectively compensating for the high brittleness of the PAA coating film and completely solving the cracking problem during high areal density coating; Finally, by reducing Joule heating during cycling through low resistivity, combined with the strong adhesion of PAA, the active material is suppressed from falling off due to volume expansion during charging and discharging, thereby significantly improving the cycle life of the battery.

[0022] 3. This invention synergistically modifies carbon nanotubes through three steps: nitrogen doping, carbon dot composite, and mercaptosilane modification. First, nitrogen doping significantly enhances the intrinsic conductivity of carbon nanotubes, thereby reducing resistance and improving electrochemical performance. Simultaneously, defects formed by nitrogen atoms on the carbon nanotube surface and nitrogen-containing functional groups (such as pyridine nitrogen and pyrrole nitrogen) act as active anchors, forming strong hydrogen bonds with carboxyl and amino functional groups on the carbon dot surface, significantly enhancing the interfacial bonding between N-CNTs and carbon dots, ensuring the stability of the composite structure. Second, the polar groups on the carbon dot surface further synergize with the nitrogen doping sites to effectively prevent carbon nanotube aggregation, improving their dispersion uniformity in the slurry. Furthermore, the sulfonic acid groups (-SO3H) in the carbon dots act as strong anionic groups, promoting rapid lithium-ion transport, reducing interfacial impedance, and improving electrochemical performance. Finally, the mercapto groups in mercaptopolyethylene glycol silane form strong Cu-S chemical bonds with the copper foil, firmly anchoring the three-dimensional conductive network to the current collector, while the polyethylene glycol segments impart good flexibility to the electrode. The three-step modification process works synergistically to give the modified carbon nanotubes a highly efficient conductive network, excellent dispersibility, rapid ion transport capability, and strong interfacial anchoring force. This allows for deep compatibility with the PAA binder system, thereby significantly reducing electrode resistivity, improving peel strength, inhibiting coating cracking, and greatly enhancing the cycle life of the battery. Attached Figure Description

[0023] Figure 1 This describes the coating cracking of the negative electrode sheet in Embodiment 1 of the present invention. Figure 2 The image shows the coating cracking of the negative electrode sheet in Comparative Example 7 of this invention. Detailed Implementation

[0024] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, specific embodiments of the present invention will be described in detail below.

[0025] In a first aspect, the present invention provides a high cycle life lithium-ion battery negative electrode sheet, comprising a negative electrode slurry and copper foil; the negative electrode slurry comprises the following components by weight percentage: 49%-54% negative electrode solid material, the balance being deionized water; the negative electrode solid material comprises the following components by weight percentage: graphite 94.6-97.5%, carbon black 0.5-1.2%, modified carbon nanotubes 0.05-0.1%, polyacrylic acid 0.8-1.4%, sodium carboxymethyl cellulose 0.1-1.5%, styrene-butadiene rubber 0.8-1.2%; the sum of the weight percentages of all components of the negative electrode solid material is 100%.

[0026] This invention ensures a balance between coating fluidity and drying efficiency by controlling the solid content of the negative electrode slurry within a suitable range of 49%-54%. Graphite, as the main active material, provides high capacity, while carbon black fills the gaps between particles to construct a basic conductive network. Modified carbon nanotubes, with their one-dimensional aspect ratio, synergistically form a line-point three-dimensional conductive framework with carbon black, significantly reducing the electrode resistivity. Polyacrylic acid forms strong hydrogen bonds with copper foil through carboxyl groups and interacts with the surface active groups of modified carbon nanotubes, giving the electrode high peel strength and flexibility. Sodium carboxymethyl cellulose adjusts the slurry viscosity and prevents sedimentation, while styrene-butadiene rubber further enhances the bonding network. The components work synergistically in the stated ratio to achieve a comprehensive effect of low resistivity, high peel strength, excellent crack resistance, and long cycle life.

[0027] In some embodiments, the polyacrylic acid has a weight-average molecular weight of 300,000-800,000 and a glass transition temperature of 90-110°C. This molecular weight and glass transition temperature range give the polyacrylic acid both moderate solution viscosity and film-forming flexibility, allowing it to be uniformly dispersed in the slurry and effectively bind active materials. It also avoids insufficient bonding strength due to excessively low molecular weight or gelation and coating difficulties due to excessively high molecular weight. Simultaneously, the suitable glass transition temperature ensures the dimensional stability and flexibility of the electrode during drying and rolling processes, preventing cracking.

[0028] Carbon nanotubes possess ultra-high aspect ratios and excellent conductivity, enabling the construction of line-point three-dimensional conductive networks between graphite particles, significantly reducing electrode resistivity. However, the original carbon nanotubes exhibit strong surface inertness and are prone to aggregation, resulting in poor dispersibility in aqueous slurries. Furthermore, they lack chemical bonding with copper foil current collectors, hindering their ability to fully realize their conductivity-enhancing and bridging toughening effects. Therefore, this invention employs the following multi-step modification process for carbon nanotubes.

[0029] In some embodiments, the modified carbon nanotubes are prepared by: S1. Dissolve citric acid and 3-amino-2-sulfopropionic acid in deionized water, sonicate until dissolved, heat to react, let stand, cool to room temperature, filter and collect the filtrate to obtain carbon dots; The above steps involve the hydrothermal carbonization reaction of citric acid and 3-amino-2-sulfonylpropionic acid to prepare carbon dots with a surface rich in carboxyl, amino, and sulfonic acid groups. These polar functional groups not only endow the carbon dots with good water solubility and reactivity, but also provide abundant chemical anchors for subsequent composite with carbon nanotubes. At the same time, the sulfonic acid groups, as strong anionic groups, can promote the rapid transport of lithium ions, laying the foundation for the functional modification of carbon nanotubes. S2. Mix N-CNTs and carbon dots, ultrasonically stir, centrifuge, and dry to obtain N-CNTs-carbon dots; The above steps involve mixing nitrogen-doped carbon nanotubes with carbon dots using ultrasound. By utilizing the hydrogen bonds and π-π interactions between the polar groups on the carbon dot surface and the surface defects and nitrogen-containing functional groups of N-CNTs, the carbon dots are uniformly adsorbed onto the carbon nanotube surface, forming a stable N-CNTs-carbon dot composite structure. This effectively prevents carbon nanotube aggregation, improves its dispersion uniformity in the slurry, and synergistically constructs an electron / ion dual conduction channel with the nitrogen doping sites. S3. Add N-CNTs-carbon dots to deionized water, stir, then add mercapto-polyethylene glycol silane, stir to react, filter, and dry to obtain modified carbon nanotubes.

[0030] The above steps further introduce mercapto-polyethylene glycol silane, whose silane end undergoes a condensation reaction with the hydroxyl groups on the carbon nanotube surface to form covalent bonds, anchoring the mercapto and flexible polyethylene glycol segments to the composite surface. The mercapto forms strong Cu-S chemical bonds with the copper foil to achieve a firm anchoring of the conductive network, while the polyethylene glycol segments impart good flexibility to the electrode to buffer volume expansion stress. Thus, the carbon nanotubes have undergone three synergistic modifications through nitrogen doping, carbon dot composite, and mercapto-silane modification, resulting in high conductivity, excellent dispersibility, rapid ion transport capability, and strong interfacial anchoring force. This makes them deeply compatible with the PAA binder system, thereby significantly reducing electrode resistivity, improving peel strength, inhibiting coating cracking, and extending battery cycle life.

[0031] In some embodiments, in step S1, the ratio of citric acid, 3-amino-2-sulfonylpropionic acid, and deionized water is 5g:4-5g:50mL. This ratio ensures a stoichiometric balance between the carbon source and nitrogen and sulfur sources in carbon dot synthesis, resulting in a suitable density of carboxyl, amino, and sulfonic acid functional groups on the carbon dot surface. Insufficient citric acid leads to low carbon dot yield and an incomplete carbon skeleton, while insufficient 3-amino-2-sulfonylpropionic acid results in inadequate functional group grafting, while excessive 3-amino-2-sulfonylpropionic acid can easily cause excessive cross-linking, leading to an increase in carbon dot particle size.

[0032] In some embodiments, in step S1, the heating reaction temperature is 170-190°C and the time is 5-8 hours. This temperature and time range allows the precursor to be fully carbonized and retains active functional groups, resulting in structurally stable and surface-functionalized carbon dots. If the reaction temperature is too low or the time is too short, incomplete carbonization and insufficient functional group transformation will occur. If the temperature is too high or the time is too long, excessive removal of functional groups will occur, carbon dots will agglomerate, or even graphitize to an excessive degree, weakening their subsequent recombination with carbon nanotubes and ion conduction capabilities.

[0033] In some embodiments, the method for preparing the N-CNTs in step S2 is as follows: S21. Add multi-walled carbon nanotubes to nitric acid, stir to react, wash, and dry to obtain carbon oxide nanotubes. This step utilizes the strong oxidizing properties of nitric acid to introduce oxygen-containing functional groups such as carboxyl (-COOH) and hydroxyl (-OH) groups into defect sites on the surface of carbon nanotubes. On the one hand, the introduced polar functional groups, such as carboxyl and hydroxyl groups, significantly enhance the hydrophilicity of carbon nanotubes, greatly improving their dispersibility in aqueous slurries and avoiding agglomeration problems in subsequent processing. On the other hand, these functional groups serve as active sites for subsequent nitrogen doping reactions, effectively anchoring the nitrogen source and laying the foundation for uniform nitrogen atom incorporation. Simultaneously, the generation of oxygen-containing functional groups creates additional defect sites on the carbon nanotube surface, which is beneficial for improving lithium storage capacity and ion transport efficiency.

[0034] S22. Add carbon nanotubes and melamine to an aqueous ethanol solution, stir until the solvent is completely evaporated, anneal under nitrogen, wash, and dry to obtain N-CNTs.

[0035] The above steps achieve nitrogen doping through melamine-assisted high-temperature annealing, introducing nitrogen-containing functional groups such as pyridine nitrogen and pyrrole nitrogen onto the surface of carbon nanotubes. These nitrogen-containing functional groups can act as active anchors to form strong hydrogen bonds with functional groups such as carboxyl and amino groups on the surface of carbon dots, significantly enhancing the interfacial bonding force between N-CNTs and carbon dots and ensuring the stability of the composite structure. At the same time, nitrogen doping changes the electronic structure of carbon nanotubes, improving their intrinsic conductivity. The sulfonic acid groups in the carbon dots act as strong anionic groups, promoting the rapid transport of lithium ions. The two work together to form an electron / ion dual conduction channel.

[0036] In some embodiments, in step S21, the ratio of the multi-walled carbon nanotube to nitric acid is 1g:80-100mL. This ratio ensures that the nitric acid fully wets and uniformly oxidizes the surface of the carbon nanotubes, introducing an appropriate amount of oxygen-containing functional groups without excessively etching the tube wall structure. If the amount of nitric acid is too small, the oxidation will be insufficient, the functional groups will not be introduced in enough quantity, and the dispersibility and subsequent nitrogen doping efficiency will be affected. If the amount of nitric acid is too large, the oxidation will be excessive, leading to an increase in structural defects in the carbon nanotubes, a decrease in the aspect ratio, and damage to the intrinsic conductivity.

[0037] In some embodiments, in step S21, the temperature of the stirring reaction is 70-80°C and the time is 5-7 hours. This temperature and time range can gently achieve oxidation of the carbon nanotube surface, introducing sufficient functional groups while avoiding excessive etching of the tube wall; if the temperature is too low or the time is too short, the oxidation will be incomplete and the functional group density will be insufficient, while if the temperature is too high or the time is too long, the carbon nanotubes will be severely etched and the conductivity will decrease significantly.

[0038] In some embodiments, in step S22, the ratio of carbon nanotubes, melamine, and ethanol-water solution is 1g:0.6-0.8g:100mL; the volume ratio of anhydrous ethanol to deionized water in the ethanol-water solution is 1:1. This ratio ensures that melamine is uniformly coated on the surface of carbon nanotubes and that there is sufficient supply of nitrogen dopant during annealing. The ethanol / water mixed solvent facilitates the dissolution of melamine and the dispersion of carbon nanotubes. If there is too little melamine, the amount of nitrogen doping will be insufficient and the improvement in conductivity will be limited; if there is too much melamine, carbon impurities will remain after annealing. Too much water in the solvent will result in insufficient dissolution of melamine, and too much ethanol will result in poor dispersion of carbon nanotubes.

[0039] In some embodiments, in step S22, the stirring temperature is 80°C; the annealing temperature is 650-700°C, and the time is 1-2 hours. This temperature and time range can effectively incorporate nitrogen atoms into the carbon nanotube lattice and control the ratio of pyridine nitrogen, pyrrole nitrogen, and graphitic nitrogen, while maintaining the integrity of the carbon nanotube structure. If the temperature is too low or the time is too short, nitrogen doping will be insufficient; if the temperature is too high or the time is too long, nitrogen-containing functional groups will decompose and the carbon nanotube structure will collapse.

[0040] In some embodiments, in step S2, the ratio of N-CNTs to carbon dots is 1g:80-100mL. This ratio ensures that carbon dots form a uniform adsorption layer on the surface of N-CNTs without excessive accumulation; too few carbon dots result in insufficient dispersion enhancement and ion conduction promotion effects, while too many carbon dots lead to multilayer adsorption or even aggregation, clogging the carbon nanotube pores or increasing interfacial resistance.

[0041] In some embodiments, in step S3, the ratio of N-CNTs-carbon dots, deionized water, and mercaptopolyethylene glycol silane is 1g:10mL:0.05-0.1g. This ratio achieves a single-layer uniform grafting of mercaptopolyethylene glycol silane onto the surface of N-CNTs-carbon dots; if there is too little silane, there will be insufficient mercapto anchoring points, low polyethylene glycol segment coverage, and limited improvement in flexibility; if there is too much silane, multi-layer grafting will result in excessive steric hindrance, and the mercapto groups will be embedded, failing to effectively anchor the copper foil.

[0042] In some embodiments, in step S3, the stirring reaction is carried out at room temperature for 6-8 hours. This time range ensures that the mercaptopolyethylene glycol silane reacts fully with the hydroxyl groups on the surface of N-CNTs-carbon dots to reach grafting equilibrium; if the time is too short, the grafting will be insufficient and the modification effect will be poor, while if the time is too long, self-condensation will occur between silane molecules or the grafted silane will hydrolyze and fall off.

[0043] Secondly, the present invention provides a method for preparing a high cycle life lithium-ion battery negative electrode sheet, comprising the following steps: (1) Add polyacrylic acid to deionized water and stir to dissolve for 2 hours to prepare a glue solution with a solid content of 1%-3%; The above steps pre-dissolve polyacrylic acid to prepare a glue solution, allowing the polymer molecular chains to fully extend and form a uniform dispersion system. This avoids local agglomeration when powder is added directly later, laying the foundation for obtaining a uniform and stable bonding network. At the same time, the appropriate solid content ensures that the glue solution has suitable fluidity, making it easy to mix with other components later.

[0044] (2) Take 70% of the total amount of graphite and add it to the mixing tank along with all the conductive carbon black and all the sodium carboxymethyl cellulose. Then add deionized water and modified carbon nanotubes, knead and stir, then add the remaining 30% of graphite and continue stirring until uniform. Finally, add styrene-butadiene rubber and stir quickly until uniform to obtain the composite slurry. The above steps first involve forcefully kneading 70% graphite with all carbon black, sodium carboxymethyl cellulose, and modified carbon nanotubes at high viscosity. High shear force is used to uniformly anchor the modified carbon nanotubes to the surface of the graphite particles and construct a line-point three-dimensional conductive framework. Then, the remaining 30% graphite is added to dilute and adjust the overall viscosity of the slurry. Finally, styrene-butadiene rubber is added to prevent it from being damaged by high shear. This sequence ensures the integrity and uniformity of the conductive network, while protecting the latex particle structure of the styrene-butadiene rubber, allowing the conductive agent, active material, and binder to form an optimal spatial distribution.

[0045] (3) Add 20% of the total amount of adhesive to the composite slurry, stir and disperse, then add the remaining 80% of adhesive, adjust the viscosity, and degas under vacuum to obtain the negative electrode slurry; The above steps involve adding the polyacrylic acid adhesive in two stages. The first 20% is added and dispersed by high-speed stirring, allowing the binder to preferentially adsorb onto the surface of the active material and conductive agent to form a pre-coating layer. This effectively inhibits particle agglomeration and improves interfacial compatibility. The remaining 80% of the adhesive is then added to adjust to the target viscosity. This avoids localized gelation or uneven dispersion caused by adding the adhesive all at once, while precisely controlling the rheological properties of the slurry to ensure good leveling and stability during coating.

[0046] (4) The negative electrode slurry is coated onto copper foil, dried, and then rolled to obtain the negative electrode sheet.

[0047] The above steps involve coating the slurry onto the copper foil and then drying it to evaporate the moisture. This allows the carboxyl groups on the polyacrylic acid molecular chains to form strong hydrogen bonds with the copper foil surface, thereby enhancing the peel strength. At the same time, the flexible polyethylene glycol segments and fiber structure in the modified carbon nanotubes act as bridges and toughens the electrode, effectively buffering drying shrinkage stress and inhibiting cracking. Rolling control of compaction density ensures close contact between active materials and with the current collector, further reducing the electrode resistivity and improving structural stability.

[0048] In some embodiments, in step (3), the viscosity is 4000-8000 mPa·s. This viscosity range allows the slurry to have both good dispersion stability and coating leveling properties, avoiding both excessively low viscosity which leads to particle sedimentation, sagging and uneven thickness during coating, and excessively high viscosity which causes difficulties in defoaming, increased coating resistance and streaks on the electrode surface, thereby ensuring uniform coating, electrode consistency and excellent processing yield.

[0049] The specific embodiments of the present invention will be described in detail below, but it should be understood that the scope of protection of the present invention is not limited to the specific embodiments.

[0050] In this invention, the multi-walled carbon nanotubes have a diameter of 10 nm and a length of 10 μm.

[0051] In this invention, the molecular weight of the mercaptopolyethylene glycol silane is 1K.

[0052] Preparation Example 1 The method for preparing the modified carbon nanotubes in this preparation example is as follows: S1. Dissolve 5g of citric acid and 4g of 3-amino-2-sulfopropionic acid in 50mL of deionized water, sonicate until dissolved, heat at 170℃ for 5h, let stand, cool to room temperature, filter and collect the filtrate to obtain carbon dots. S2. Mix 1g of N-CNTs and 80mL of carbon dots, sonicate for 3h and stir for 3h, centrifuge and dry to obtain N-CNTs-carbon dots; S3. Add 1g of N-CNTs-carbon dots to 10mL of deionized water and stir. Then add 0.05g of mercaptopolyethylene glycol silane and stir at room temperature for 6h. Filter and dry to obtain modified carbon nanotubes.

[0053] The preparation method of N-CNTs is as follows: S21. Add 1g of multi-walled carbon nanotubes to 80mL of nitric acid, stir at 70℃ for 5h, wash and dry to obtain carbon oxide nanotubes. S22. Add 1g of carbon oxide nanotubes and 0.6g of melamine to 100mL of ethanol aqueous solution. The volume ratio of anhydrous ethanol to deionized water in the ethanol aqueous solution is 1:1. Stir at 80℃ until the solvent is completely evaporated. Anneal at 650℃ for 1h under nitrogen atmosphere. Wash and dry to obtain N-CNTs.

[0054] Preparation Example 2 The method for preparing the modified carbon nanotubes in this preparation example is as follows: S1. Dissolve 5g of citric acid and 4.5g of 3-amino-2-sulfopropionic acid in 50mL of deionized water, sonicate until dissolved, heat at 180℃ for 7h, let stand, cool to room temperature, filter and collect the filtrate to obtain carbon dots. S2. Mix 1g of N-CNTs and 90mL of carbon dots, sonicate for 3h and stir for 3h, centrifuge and dry to obtain N-CNTs-carbon dots; S3. Add 1g of N-CNTs-carbon dots to 10mL of deionized water and stir. Then add 0.08g of mercaptopolyethylene glycol silane and stir at room temperature for 7h. Filter and dry to obtain modified carbon nanotubes.

[0055] The preparation method of N-CNTs is as follows: S21. Add 1g of multi-walled carbon nanotubes to 90mL of nitric acid, stir at 75℃ for 6h, wash and dry to obtain carbon oxide nanotubes. S22. Add 1g of carbon oxide nanotubes and 0.7g of melamine to 100mL of ethanol aqueous solution. The volume ratio of anhydrous ethanol to deionized water in the ethanol aqueous solution is 1:1. Stir at 80℃ until the solvent is completely evaporated. Anneal at 680℃ for 1.5h under nitrogen atmosphere. Wash and dry to obtain N-CNTs.

[0056] Preparation Example 3 The method for preparing the modified carbon nanotubes in this preparation example is as follows: S1. Dissolve 5g of citric acid and 5g of 3-amino-2-sulfopropionic acid in 50mL of deionized water, sonicate until dissolved, heat at 190℃ for 8h, let stand, cool to room temperature, filter and collect the filtrate to obtain carbon dots. S2. Mix 1g of N-CNTs and 100mL of carbon dots, sonicate for 3h and stir for 3h, centrifuge and dry to obtain N-CNTs-carbon dots; S3. Add 1g of N-CNTs-carbon dots to 10mL of deionized water and stir. Then add 0.1g of mercaptopolyethylene glycol silane and stir at room temperature for 8h. Filter and dry to obtain modified carbon nanotubes.

[0057] The preparation method of N-CNTs is as follows: S21. Add 1g of multi-walled carbon nanotubes to 100mL of nitric acid, stir at 80℃ for 7h, wash and dry to obtain carbon oxide nanotubes. S22. Add 1g of carbon oxide nanotubes and 0.8g of melamine to 100mL of ethanol aqueous solution. The volume ratio of anhydrous ethanol to deionized water in the ethanol aqueous solution is 1:1. Stir at 80℃ until the solvent is completely evaporated. Anneal at 700℃ for 2h under nitrogen. Wash and dry to obtain N-CNTs.

[0058] Compare with Example 1 The only difference between this comparative example and preparation example 1 is that, in step S3, an equal amount of 3-mercaptopropyltrimethoxysilane was used to replace mercaptopolyethylene glycol silane.

[0059] Compare with Example 2 The only difference between this comparative example and preparation example 1 is that step S3 is omitted, and N-CNTs-carbon dots are used as modified carbon nanotubes.

[0060] Compare with Example 3 The only difference between this comparative example and preparation example 1 is that multi-walled carbon nanotubes were used instead of N-CNTs. The specific steps are as follows: S1. Dissolve 5g of citric acid and 4g of 3-amino-2-sulfopropionic acid in 50mL of deionized water, sonicate until dissolved, heat at 170℃ for 5h, let stand, cool to room temperature, filter and collect the filtrate to obtain carbon dots. S2. Mix 1g of multi-walled carbon nanotubes and 80mL of carbon dots, sonicate for 3h and stir for 3h, centrifuge and dry to obtain multi-walled carbon nanotubes-carbon dots. S3. Add 1g of multi-walled carbon nanotubes-carbon dots to 10mL of deionized water, stir, then add 0.05g of mercaptopolyethylene glycol silane, stir and react at room temperature for 6h, filter, dry, and obtain modified carbon nanotubes.

[0061] Compare with Example 4 The only difference between this comparative example and preparation example 1 is that step S3 is omitted, and 3-amino-2-sulfopropionic acid in step S1 is replaced with an equal amount of glycine. The specific steps are as follows: S1. Dissolve 5g citric acid and 4g glycine in 50mL deionized water, sonicate until dissolved, heat at 170℃ for 5h, let stand, cool to room temperature, filter and collect the filtrate to obtain carbon dots; S2. Mix 1g of N-CNTs and 80mL of carbon dots, sonicate for 3h and stir for 3h, centrifuge and dry to obtain modified carbon nanotubes. The preparation method of N-CNTs is as follows: S21. Add 1g of multi-walled carbon nanotubes to 80mL of nitric acid, stir at 70℃ for 5h, wash and dry to obtain carbon oxide nanotubes. S22. Add 1g of carbon oxide nanotubes and 0.6g of melamine to 100mL of ethanol aqueous solution. The volume ratio of anhydrous ethanol to deionized water in the ethanol aqueous solution is 1:1. Stir at 80℃ until the solvent is completely evaporated. Anneal at 650℃ for 1h under nitrogen atmosphere. Wash and dry to obtain N-CNTs.

[0062] Compare with Example 5 The only difference between this comparative example and preparation example 1 is that N-CNTs were directly used as modified carbon nanotubes.

[0063] Compare with Example 6 The only difference between this comparative example and preparation example 1 is that multi-walled carbon nanotubes were directly used as modified carbon nanotubes.

[0064] Example 1 This invention provides a high cycle life lithium-ion battery negative electrode sheet, comprising a negative electrode slurry and copper foil; the negative electrode slurry comprises the following components by weight percentage: 49% negative electrode solid material, and the balance 51% deionized water; the negative electrode solid material comprises the following components by weight percentage: 96.7% graphite, 0.8% carbon black, 0.05% modified carbon nanotubes obtained in Preparation Example 1, 1.0% polyacrylic acid, 0.65% sodium carboxymethyl cellulose, and 0.8% styrene-butadiene rubber; The polyacrylic acid has a weight-average molecular weight of 500,000 and a glass transition temperature of 100°C.

[0065] Its preparation method is as follows: (1) Add polyacrylic acid to deionized water and stir to dissolve for 2 hours to prepare a glue solution with a solid content of 2%; (2) Take 70% of the total amount of graphite and add it to the mixing tank along with all the conductive carbon black and all the sodium carboxymethyl cellulose. Then add deionized water and modified carbon nanotubes, knead and stir, then add the remaining 30% of graphite and continue stirring until uniform. Finally, add styrene-butadiene rubber and stir quickly until uniform to obtain the composite slurry. (3) Add 20% of the total amount of adhesive to the composite slurry, stir and disperse, then add the remaining 80% of adhesive, adjust the viscosity to 5000 mPa·s, degas under vacuum, and obtain the negative electrode slurry; (4) The negative electrode slurry is coated onto copper foil, dried, and then rolled to obtain the negative electrode sheet.

[0066] Example 2 This invention provides a high cycle life lithium-ion battery negative electrode sheet, comprising a negative electrode slurry and copper foil; the negative electrode slurry comprises the following components by weight percentage: 51% negative electrode solid material, and the balance 49% deionized water; the negative electrode solid material is composed of the following components by weight percentage: 96.2% graphite, 1.0% carbon black, 0.07% modified carbon nanotubes obtained in Preparation Example 2, 1.2% polyacrylic acid, 0.33% sodium carboxymethyl cellulose, and 1.2% styrene-butadiene rubber; The polyacrylic acid has a weight-average molecular weight of 600,000 and a glass transition temperature of 95°C.

[0067] Its preparation method is as follows: (1) Add polyacrylic acid to deionized water and stir to dissolve for 2 hours to prepare a glue solution with a solid content of 2%; (2) Take 70% of the total amount of graphite and add it to the mixing tank along with all the conductive carbon black and all the sodium carboxymethyl cellulose. Then add deionized water and modified carbon nanotubes, knead and stir, then add the remaining 30% of graphite and continue stirring until uniform. Finally, add styrene-butadiene rubber and stir quickly until uniform to obtain the composite slurry. (3) Add 20% of the total amount of adhesive to the composite slurry, stir and disperse, then add the remaining 80% of adhesive, adjust the viscosity to 6000 mPa·s, degas under vacuum, and obtain the negative electrode slurry; (4) The negative electrode slurry is coated onto copper foil, dried, and then rolled to obtain the negative electrode sheet.

[0068] Example 3 This invention provides a high cycle life lithium-ion battery negative electrode sheet, comprising a negative electrode slurry and copper foil; the negative electrode slurry comprises the following components by weight percentage: 54% negative electrode solid material, and the balance being 46% deionized water; the negative electrode solid material is composed of the following components by weight percentage: 94.6% graphite, 1.2% carbon black, 0.10% modified carbon nanotubes obtained in Preparation Example 3, 1.4% polyacrylic acid, 1.5% sodium carboxymethyl cellulose, and 1.2% styrene-butadiene rubber; The polyacrylic acid has a weight-average molecular weight of 800,000 and a glass transition temperature of 110°C.

[0069] Its preparation method is as follows: (1) Add polyacrylic acid to deionized water and stir to dissolve for 2 hours to prepare a glue solution with a solid content of 2%; (2) Take 70% of the total amount of graphite and add it to the mixing tank along with all the conductive carbon black and all the sodium carboxymethyl cellulose. Then add deionized water and modified carbon nanotubes, knead and stir, then add the remaining 30% of graphite and continue stirring until uniform. Finally, add styrene-butadiene rubber and stir quickly until uniform to obtain the composite slurry. (3) Add 20% of the total amount of adhesive to the composite slurry, stir and disperse, then add the remaining 80% of adhesive, adjust the viscosity to 7500 mPa·s, degas under vacuum, and obtain the negative electrode slurry; (4) The negative electrode slurry is coated onto copper foil, dried, and then rolled to obtain the negative electrode sheet.

[0070] Example 4 The only difference between this embodiment and Example 3 is that the modified carbon nanotubes obtained in Example 1 are replaced with an equal amount of the modified carbon nanotubes obtained in Example 2.

[0071] Example 5 The only difference between this embodiment and Example 3 is that the modified carbon nanotubes obtained in Example 1 are replaced with an equal amount of the modified carbon nanotubes obtained in Example 3.

[0072] Comparative Example 1 The only difference between this comparative example and Example 1 is that the modified carbon nanotubes obtained in Preparation Example 1 were replaced with an equal amount of the modified carbon nanotubes obtained in Control Example 1.

[0073] Comparative Example 2 The only difference between this comparative example and Example 1 is that the modified carbon nanotubes obtained in Preparation Example 1 were replaced with an equal amount of the modified carbon nanotubes obtained in Control Example 2.

[0074] Comparative Example 3 The only difference between this comparative example and Example 1 is that the modified carbon nanotubes obtained in Preparation Example 1 were replaced with an equal amount of the modified carbon nanotubes obtained in Control Example 3.

[0075] Comparative Example 4 The only difference between this comparative example and Example 1 is that the modified carbon nanotubes obtained in Preparation Example 1 were replaced with an equal amount of the modified carbon nanotubes obtained in Control Example 4.

[0076] Comparative Example 5 The only difference between this comparative example and Example 1 is that the modified carbon nanotubes obtained in Preparation Example 1 were replaced with an equal amount of the modified carbon nanotubes obtained in Control Example 5.

[0077] Comparative Example 6 The only difference between this comparative example and Example 1 is that the modified carbon nanotubes obtained in Preparation Example 1 were replaced with an equal amount of the modified carbon nanotubes obtained in Control Example 6.

[0078] Comparative Example 7 This comparative example provides a conventional lithium-ion battery negative electrode sheet, including a negative electrode slurry and copper foil; the negative electrode slurry includes the following components by weight percentage: 49% negative electrode solids and the balance 51% deionized water; the negative electrode solids include the following components by weight percentage: 96% graphite, 1% conductive carbon black, 1.2% sodium carboxymethyl cellulose (CMC), and 1.8% styrene-butadiene rubber (SBR).

[0079] The preparation method is as follows: CMC is added to deionized water and stirred to dissolve, then graphite and carbon black are added, stirred evenly, and then SBR emulsion is added. Stirring is continued to obtain a negative electrode slurry; the slurry is coated on copper foil, dried, and then rolled to obtain a negative electrode sheet.

[0080] The negative electrode sheets obtained in Examples 1-5 and Comparative Examples 1-7 were subjected to performance tests. The test items are as follows, and the test results are shown in Table 1. Figure 1 and Figure 2 As shown: (1) Resistivity test: Under normal humidity and room temperature of 25℃, select flat and defect-free electrode sheets to be tested, and use a four-probe resistivity tester to test the resistivity of the electrode sheet. Before the test, accurately measure the thickness of the electrode sheet, select multiple test points in different areas of the electrode sheet for testing, remove abnormal data and take the average value to obtain the final resistivity of the electrode sheet. (2) Peel strength test: The negative electrode sheet to be tested is cut into samples of uniform specifications. Under normal temperature and pressure, the electrode sheet peel strength tester is used to perform a 180° peel test. The electrode sheet coating surface is attached with special tape and the peel test is performed at a constant tensile speed. Each group of samples is tested multiple times and the average peel force is taken to calculate the peel strength per unit width. (3) Coating cracking: After drying, the electrode sheets are visually inspected to observe whether there are macroscopic defects such as peeling, cracking, and powdering on the whole, edge and surface of the electrode sheets. The crack resistance and integrity of the ultra-thick electrode sheets under different processes and formulations are determined and divided into "no cracking", "fine cracks", "slight cracking" and "edge cracking" in order from best to worst.

[0081] (4) Cyclic performance test: The prepared negative electrode sheet is assembled with the same positive electrode sheet into a lithium-ion battery. After liquid injection, formation and capacity testing, the battery is cycled under a constant current and constant voltage charge and discharge regime of 1C / 1C at room temperature of 25℃ or high temperature of 45℃. For lithium iron phosphate-graphite battery, the charge and discharge voltage window is 2.5-3.65V. After a single charge and discharge cycle, the battery is left to stand for a fixed interval and continuously cycled for thousands of cycles. The battery discharge capacity is recorded periodically and the capacity retention rate after 500 cycles is calculated.

[0082] Table 1

[0083] Depend on Figure 1 The results show that the negative electrode coating of Example 1 of the present invention did not crack, while the edge of Comparative Example 7 cracked. This indicates that the fiber structure of the modified carbon nanotubes plays a bridging and toughening role in the electrode, effectively making up for the defect of high brittleness of the PAA coating film and completely solving the cracking problem during high areal density coating.

[0084] As can be seen from the experimental results in Table 1, the negative electrode sheets of Examples 1-5 of the present invention exhibit excellent performance in terms of resistivity, peel strength, coating cracking, and cycle life. No coating cracking occurred in any of the examples, and the resistivity was low and the peel strength was high. Moreover, the capacity retention rate was at a high level after 500 cycles, which fully demonstrates the effectiveness and stability of the technical solution of the present invention.

[0085] Further analysis shows that in Examples 1-5, as the preparation conditions of modified carbon nanotubes were gradually optimized (from Preparation Example 1 to Preparation Example 3), the resistivity showed a continuous downward trend, the peeling force gradually increased, and the cycle life was correspondingly improved. This indicates that the present invention has a significant progressive synergistic effect on the three-step synergistic modification of carbon nanotubes by nitrogen doping-carbon dot composite-thiol silane modification. Each step of modification is indispensable and promotes each other.

[0086] Compared to the examples, the performance of each comparative example deteriorated to varying degrees: The modified carbon nanotubes (Comparative Example 1) modified with ordinary mercaptosilane without polyethylene glycol segments (Comparative Example 1) showed higher resistivity and decreased peel strength than the examples, indicating that the flexible polyethylene glycol segments play a crucial role in improving electrode flexibility and conductive network stability; Comparative Example 2, which omitted the mercaptosilane modification step (Comparative Example 2), showed significantly increased resistivity and slight cracking, demonstrating that the chemical anchoring of mercapto groups to copper foil is indispensable for reducing interfacial resistance and suppressing cracking; Comparative Example 3, which used undoped multi-walled carbon nanotubes instead of N-CNTs (Comparative Example 3), showed lower resistivity and peel strength than the examples, indicating that nitrogen doping is crucial for improving the intrinsic conductivity of carbon nanotubes and their interfacial bonding with carbon dots; and the modified carbon nanotubes (Comparative Example 4) using carbon dots without sulfonic acid groups... Example 4 showed increased resistivity and cracking, confirming that the sulfonic acid group, as an anionic group, makes a unique contribution to promoting lithium-ion transport and reducing interfacial impedance. Comparative Example 5, which directly used N-CNTs without carbon dot composite and silane modification (Comparative Example 5), and Comparative Example 6, which directly used original multi-walled carbon nanotubes (Comparative Example 6), showed further performance degradation and obvious cracking, fully demonstrating that each step of carbon dot composite and mercaptosilane modification is necessary to obtain excellent overall performance. Comparative Example 7, which completely adopted the traditional SBR+CMC bonding system without using modified carbon nanotubes, had the highest resistivity, lowest peel strength, most severe coating cracking, and shortest cycle life, further highlighting the outstanding advantages of the PAA+modified carbon nanotube synergistic system of this invention in reducing resistivity, improving peel strength, inhibiting cracking, and extending cycle life.

[0087] The above-disclosed embodiments are merely a few specific examples of the present invention. However, the embodiments of the present invention are not limited thereto, and any variations that can be conceived by those skilled in the art should fall within the protection scope of the present invention.

Claims

1. A high cycle life lithium-ion battery negative electrode sheet, characterized in that, The anode material comprises a negative electrode slurry and copper foil. The negative electrode slurry comprises the following components by weight percentage: 49%-54% negative electrode solids, with the balance being deionized water. The negative electrode solids comprise the following components by weight percentage: 94.6-97.5% graphite, 0.5-1.2% carbon black, 0.05-0.1% modified carbon nanotubes, 0.8-1.4% polyacrylic acid, 0.1-1.5% sodium carboxymethyl cellulose, and 0.8-1.2% styrene-butadiene rubber. The sum of the weight percentages of all components of the negative electrode solids is 100%.

2. The high cycle life lithium-ion battery negative electrode sheet as described in claim 1, characterized in that, The polyacrylic acid has a weight-average molecular weight of 300,000-800,000 and a glass transition temperature of 90-110℃.

3. The high cycle life lithium-ion battery negative electrode sheet as described in claim 1, characterized in that, The method for preparing the modified carbon nanotubes is as follows: S1. Dissolve citric acid and 3-amino-2-sulfopropionic acid in deionized water, sonicate until dissolved, heat to react, let stand, cool to room temperature, filter and collect the filtrate to obtain carbon dots; S2. Mix N-CNTs and carbon dots, ultrasonically stir, centrifuge, and dry to obtain N-CNTs-carbon dots; S3. Add N-CNTs-carbon dots to deionized water, stir, then add mercapto-polyethylene glycol silane, stir to react, filter, and dry to obtain modified carbon nanotubes.

4. The high cycle life lithium-ion battery negative electrode sheet as described in claim 3, characterized in that, In step S1, the ratio of citric acid, 3-amino-2-sulfopropionic acid, and deionized water is 5g:4-5g:50mL. The heating reaction is carried out at a temperature of 170-190℃ for 5-8 hours.

5. The high cycle life lithium-ion battery negative electrode sheet as described in claim 3, characterized in that, In step S2, the method for preparing the N-CNTs is as follows: S21. Add multi-walled carbon nanotubes to nitric acid, stir to react, wash, and dry to obtain carbon oxide nanotubes. S22. Add carbon nanotubes and melamine to an aqueous ethanol solution, stir until the solvent is completely evaporated, anneal under nitrogen, wash, and dry to obtain N-CNTs.

6. The high cycle life lithium-ion battery negative electrode sheet as described in claim 5, characterized in that, In step S21, the ratio of the amount of multi-walled carbon nanotubes to nitric acid is 1g:80-100mL; In step S21, the temperature of the stirring reaction is 70-80℃, and the time is 5-7h; In step S22, the ratio of carbon nanotubes, melamine, and ethanol aqueous solution is 1g:0.6-0.8g:100mL; the volume ratio of anhydrous ethanol to deionized water in the ethanol aqueous solution is 1:

1. In step S22, the stirring temperature is 80℃; the annealing temperature is 650-700℃, and the time is 1-2 hours.

7. The high cycle life lithium-ion battery negative electrode sheet as described in claim 3, characterized in that, In step S2, the ratio of N-CNTs to carbon dots is 1g:80-100mL.

8. The high cycle life lithium-ion battery negative electrode sheet as described in claim 3, characterized in that, In step S3, the ratio of N-CNTs-carbon dots, deionized water, and mercaptopolyethylene glycol silane is 1g:10mL:0.05-0.1g; The stirring reaction was carried out at room temperature for 6-8 hours.

9. A method for preparing a high cycle life lithium-ion battery negative electrode sheet, used to prepare the high cycle life lithium-ion battery negative electrode sheet according to any one of claims 1-8, characterized in that, Includes the following steps: (1) Add polyacrylic acid to deionized water and stir to dissolve for 2 hours to prepare a glue solution with a solid content of 1%-3%; (2) Take 70% of the total amount of graphite and add it to the mixing tank along with all the conductive carbon black and all the sodium carboxymethyl cellulose. Then add deionized water and modified carbon nanotubes, knead and stir, then add the remaining 30% of graphite and continue stirring until uniform. Finally, add styrene-butadiene rubber and stir evenly to obtain the composite slurry. (3) Add 20% of the total amount of adhesive to the composite slurry, stir and disperse, then add the remaining 80% of adhesive, adjust the viscosity, and degas under vacuum to obtain the negative electrode slurry; (4) The negative electrode slurry is coated onto copper foil, dried, and then rolled to obtain the negative electrode sheet.

10. The high cycle life lithium-ion battery negative electrode sheet as described in claim 9, characterized in that, In step (3), the viscosity is 4000-8000 mPa·s.